Peranan Kompetensi Pedagogik Guru Terhadap Kedisiplinan Belajar Siswa SDN 008 Kemuning Muda Kecamatan Bungaraya Kabupaten Siak - Rofiah, Rofiah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to determine the importance of teacher pedagogical competence on student learning discipline at SDN 008 Kemuning Muda, Bungaraya District, Siak Regency. This research is a qualitative descriptive study. The subjects of this research were class VI teachers, class I teachers, and the principal at SDN 008 Kemuning Muda. The data collection techniques used were observation, interviews and documentation. The main instrument is the researcher using observation guide tools, interview guidelines, document sheets. Data were analyzed through data reduction, data presentation, and drawing conclusions. The data validity checking technique uses triangulation of techniques and sources. The research results show that the importance of pedagogical competence has a big impact on student learning discipline. The research results show that the pedagogical competence of class VI teachers and class I teachers at SD Negeri 08 Kemuning Muda is quite good but not optimal. This is because the teacher's pedagogical competence makes some students disciplined in learning, but the teacher has not optimally implemented learning according to the indicators of pedagogical competence. Of the seven indicators of pedagogical competence in this research, there are 2 indicators that teachers do not yet have optimally, such as indicators of mastery of learning theories and learning principles, and assessment and evaluation of learning.